Effect of Particle Size on Young's Modulus of Carbon from Oil Palm Bunches - Deraman, Mohamad; Ismail, Mohamad Pauzi (Universiti Putra Malaysia Press, 1995)
In an effort to use oil palm empty fruit bunches (EFB) for making carbon products, EFB was ground and pelletized. The pellets were carbonized in vacuo up to 1000°C, using a heating rate of about 200°C/h. Young's modulus of the carbon pellets was measured using the ultrasonic technique. The data shows that Young's modulus is significantly dependent on the particle size of the powder used in the preparation of the green body. Young's modulus of carbon pellets made from smaller particles (70% powder with size ~ 50 11m plus 30% powder with 50 11m ~ size ~ 150 11m) and larger particles (100% powder with 50 11m ~ size ~ 150 pm) was 1.02 GPa and 0.78 GPa respectively. These values appear to be about 5 to 6 times smaller than those of the carbon samples directly prepared from the endocarp of babassu coconut and about 9 times smaller than that of the carbon product from General Electric Company.